2014
DOI: 10.1111/labr.12044
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Lifelong Learning: An Empirical Analysis of the Impact of Marriage and Children

Abstract: We use recent advances in the statistical analysis of Oaxaca–Blinder decompositions for non‐linear models to analyse the contribution of individual variables to total gender differences in training participation and duration. Results suggest that effects stemming from the intra‐household division of labour contribute significantly to gender differences, but that segregation of the labour market as well as differences in the access to training by tenure, age, occupation, profession and sectors are more importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Grönland (2012) found that female-dominated occupations, for example, secretaries and administrative assistants, generally had less AET requirements than male-dominated occupations, and women generally received less AET opportunities than men despite being employed in similar occupations overall. Huber and Huemer (2015) claimed that married women and women with children participated less in AET compared to married men and men with children. Acker (2006) found that men who were married and had children were perceived as hardworking and deserving of additional AET, whereas women who were married and had children were perceived as less serious candidates of AET.…”
Section: Introductionmentioning
confidence: 99%
“…Grönland (2012) found that female-dominated occupations, for example, secretaries and administrative assistants, generally had less AET requirements than male-dominated occupations, and women generally received less AET opportunities than men despite being employed in similar occupations overall. Huber and Huemer (2015) claimed that married women and women with children participated less in AET compared to married men and men with children. Acker (2006) found that men who were married and had children were perceived as hardworking and deserving of additional AET, whereas women who were married and had children were perceived as less serious candidates of AET.…”
Section: Introductionmentioning
confidence: 99%